IMPLEMENTASI MANAJEMN PEMASARAN JASA PENDIDIKAN DI MTs MA’ARIF 1 PONOROGO - Fahrudin, Ali; Murtadlo, Murtadlo; Handayaningrum, Warih (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Marketing management of educational services will be good if it is carried out effectively and efficiently in a professional manner. This is done as an effort to make it easier for educational institutions to market their services to the public. The purpose of this study is to describe and analyze the implementation of marketing management of educational services at MTs Ma'arif 1 Ponorogo. This research uses descriptive qualitative method. The results of this study are, MTs Ma'arif 1 Ponorogo Implements the education marketing mix as follows: (1) product strategy, (2) price strategy, (3) place strategy, (4) promotion strategy, (5) people strategy, (6 ) physical eventdance strategy, (7) process strategy. In addition, there are various developments in marketing strategies carried out by MTs Ma'arif 1 Ponorogo in the face of competition between educational institutions.